PENGARUH PEMBERIAN PELVIC ROCKING EXERCISE TERHADAP PENURUNAN NYERI PUNGGUNG BAWAH PADA IBU HAMIL - Dian Juni Ekasari; Prasida Yunita; Rachmawati Abdul Hafid (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2022)
Pregnancy is a unique experience for a woman. Back pain is a disorder that many pregnant women experience that not only occurs in certain trimesters, but can be experienced throughout pregnancy to the postnatal period.. Some ways to reduce back pain that arises is to give light exercise such as Pelvic Rocking Exercise. The purpose of this study is to obtain a source of scientific reference about the effect of pelvic rocking exercise on lower back pain reduction in pregnant women based on the results of previous studies. The research method by conducting a literature search was conducted until January 2022 through the Pubmed database and google scholar using the keyword technique pelvic rocking exercise and pain reduction using more than 25 articles as a reference source. The Pelvic rocking mechanism at the time of hip and waist rotation then at that time there will be a reduction in pressure on the waist so that the lower back muscles experience relaxation and relaxation. Pelvic rocking is a safe way to keep abdominal muscles tight, helps relieve sore back by stretching lower back muscles, pelvic shake can be used as part of a regular pregnancy exercise routine, and can also be used in back pain emergencies. Pelvic rocking can minimize and even relieve lower spinal pain at the end of pregnancy and improve body function and activity of late trimester pregnant women who are often limited to movement activities due to low back pain that often appears.